Ação antioxidante e neuroprotetora de derivados pirazolínicos inéditos - Martins, Daniele Moreira (2008)
Oxidative stress is involved in several neurodegenerative diseases, such as Alzheimer's disease, Parkinson's disease and amyotrophic lateral sclerosis. Oxidative stress seems to be involved in the pathology of dementia/amnesia. It has been suggested that oxidative stress impairs the muscarinic cholinergic system triggering Alzheimer's disease. The muscarinic antagonist scopolamine has been used to induce amnesia in animals. This experimental model has been used in screening anti-amnesic drugs that could be useful for the treatment of dementia. The aim of this study was to evaluate the possible in vitro antioxidant effect of a series of pyrazoline derivatives newly synthesized: (1) 5-hydroxy-3-methyl-5-trifluoromethyl-4,5-dihydro-1H-carbaldehyde-pyrazole, (2) 5-hydroxy-3-methyl-5- trifluoromethyl-4,5-dihydro-1H-1-acetyl-pyrazole, (3) 5-hydroxy-3-methyl-5-trifluoromethyl-4,5-dihydro-1H-carboxyamide-pyrazole, (4) 5-hydroxy-3-methyl-5-trifluoromethyl-4,5-dihydro-1H-1-benzoyl-pyrazole, (5) 5-hydroxy-3-methyl-5-trifluoromethyl-4,5-dihydro-1H-1-(2- hydroxybenzoyl)-pyrazole and (6) 5-hydroxy-3-methyl-5-trifluoromethyl-4,5-dihydro-1H-1-(4-methoxybenzoyl)-pyrazole. Besides, considering the possible involvement of oxidative stress in dementia, the compound that was the most effective in vitro was assessed concerning to its ability to prevent the memory deficit and oxidative stress in a scopolamine-induced amnesia model. Compound (5) had the highest antioxidant capacity in vitro, since it reduced lipid peroxidation (TBARS) basal and stimulated by the pro-oxidants iron, hydrogen peroxide and sodium nitroprusside, having significant effects from 15 μM onwards (p<0.05). Compound (5) also protected against hydrogen peroxide-induced glutathione oxidation, with a significant effect at the concentration of 150 μM (p<0.05). This compound also had the highest total antioxidant activity, demonstrated by its ability to remove the radical 1,1-dyphenyl-2-pycrylhydrazyl (DPPH). Compounds (1) and (4) also reduced lipid peroxidation basal and stimulated by iron and sodium nitroprusside, having significant effects from 15 μM onwards (p<0.05). Compound (2) had the highest ability to reduce iron (p<0.05). Scopolamine administration 30 min before training session resulted in shorter latency to step-down during the test session of the inhibitory avoidance task (p<0.05). Pretreatment with pyrazole compound (5) had no effect per se on the step-down latency. However, pretreatment with compound (5) (100 μmol/kg) 30 min before scopolamine did prevent the amnesic effect of scopolamine (p<0.05). No significant effect of scopolamine or pyrazole treatment was observed on any of the oxidative stress markers evaluated (thiobarbituric acid reactive substances, non-protein sulfhydrylic groups content and activity of enzymes superoxide dismutase and catalase) suggesting that the protective effect of compound (5) was not related to a possible antioxidant activity. Results revealed that pyrazole compound (5) has in vitro antioxidant activity as well as neuroprotective activity in a model of amnesia. These findings suggest that compound (5) could be a promising drug for the treatment of Alzheimer´s disease. However, further studies are needed to elucidate the mechanisms involved in the antiamnesic effect of this compound, as well as its effect on other dementia models.